Chemistry for Sustainable Development in Africa 2012
DOI: 10.1007/978-3-642-29642-0_3
|View full text |Cite
|
Sign up to set email alerts
|

Role of Flavonoid and Isoflavonoid Molecules in Symbiotic Functioning and Host-Plant Defence in the Leguminosae

Abstract: Inoculating symbiotic legumes with infective rhizobial symbionts increases the nod-gene-inducing activity of root exudates, and alters the profile of nod gene inducers. The application of Sinorhizobium meliloti cells to the roots of alfalfa seedlings specifically causes the release of the aglycone and glycoside forms of the phytoalex in medicarpin, and a formononetin-O-(6 00 -O-malnylglycoside). Similarly, in the presence of Rhizobium leguminosarum biovar phaseoli bacteria, root exudates of common bean also co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 78 publications
1
1
0
Order By: Relevance
“…The production of phenolic compounds can activate the resistance system and provide bioprotection to plants during pathogen stress, and some polyphenols may act as antioxi-dants [37]. In the present study, the highest phenolic production was observed in the roots of plants inoculated with F. solani f. sp.…”
Section: Discussionsupporting
confidence: 50%
“…The production of phenolic compounds can activate the resistance system and provide bioprotection to plants during pathogen stress, and some polyphenols may act as antioxi-dants [37]. In the present study, the highest phenolic production was observed in the roots of plants inoculated with F. solani f. sp.…”
Section: Discussionsupporting
confidence: 50%
“…Seed accumulation of high amounts of phenolic compounds is toxic to bruchid [ Callosobruchus maculatus (Fabricius 1775)] and provides resistance to storage pests in cowpea [ Vigna unguiculata (L.) Walp], chickpea ( Cicer arietinum L.), and soybean (Sharma and Thakur, 2014 ). Furthermore, flavonoids and isoflavonoids are considered to have major roles in host plant defense in the Fabaceae family (Mapope and Dakora, 2013 ). For example, the specific isoflavone content in legumes is strongly related to resistance to pathogens (Treutte, 2006 ).…”
Section: Factors Influencing Accumulation Of Phenylpropanoidsmentioning
confidence: 99%